PENGARUH LOKASI PROMOSI PENJUALAN DAN SERVICE QUALITY TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA MIE RATU SITUBONDO - Jamilah, Alfi Wahidatul; Wahyuni, Ika; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of location, sales promotion, and service quality on repurchase interest through customer satisfaction as an intervening variable at Micro, Small and Medium Enterprises. Mie Ratu Situbondo. The research method used is quantitative with a survey approach to 97 respondents randomly selected from the population of Mie Ratu Situbondo consumers. Data were collected through a questionnaire and analyzed using SmartPLS 3.0 to test the validity, reliability, and relationship between variables. The results showed that sales promotion and service quality have a significant effect on customer satisfaction, while location has no significant effect. In addition, service quality also has a significant effect on repurchase intention, while location and sales promotion do not show a significant effect. Customer satisfaction as an intervening variable has no significant effect on repurchase intention, as well as the indirect effect of location, sales promotion, and service quality through customer satisfaction. This research provides practical implications for Mie Ratu Situbondo to focus more on improving service quality and sales promotion strategies to increase consumer satisfaction and repurchase interest. The findings also enrich the literature related to factors that influence consumer satisfaction and repurchase intention in the context of culinary Micro, Small and Medium Enterprises.